Magnetic Resonance Imaging of Hippocampal Subfields in Posttraumatic Stress Disorder - Wang, Zhen (2010)
CONTEXT: Most neuroimaging studies of posttraumatic stress disorder (PTSD) have focused on potential abnormalities in the whole hippocampus, but the subfields of this structure, which have distinctive histological characteristics and specialized functions, have not been investigated. Studies of individual subfields may clarify the role of the hippocampus in PTSD. OBJECTIVE: To determine if PTSD is associated with structural alterations in specific subfields of the hippocampus. DESIGN: Case-control study. PARTICIPANTS: A total of 17 male veterans with combat trauma and PTSD (mean [SD] age, 41[12] years) and 19 age-matched male veterans without PTSD who were recruited from the outpatient mental health clinic of the San Francisco Veterans Affairs Medical Center and by advertising in the community. INTERVENTIONS: High-resolution magnetic resonance imaging at 4 T. MAIN OUTCOME MEASURE: Volumes of hippocampal subfields. RESULTS: Posttraumatic stress disorder was associated with 11.4%(1.5%) (P = .02) smaller mean (SD) cornu ammonis 3 (CA3)/dentate gyrus subfield volumes, irrespective of age-related alterations, whereas other subfields were spared. Age was associated with reduced volume of the CA1 subfield (P = .03). Total hippocampal volume was also reduced in PTSD by a mean (SD) of 6.5%(0.6%) but, related to both PTSD (P = .05) and age (P = .01), was consistent with the measurements in the subfields. CONCLUSIONS: The findings indicate for the first time in humans that PTSD is associated with selective volume loss of the CA3/dentate gyrus subfields, consistent with animal studies, implying that chronic stress suppresses neurogenesis and dendritic branching in these structures.